NLRP3-Inflammasome Activating DAMPs Stimulate an Inflammatory Response in Glia in the Absence of Priming Which Contributes to Brain Inflammation after Injury - Savage, Catherine D.; Lopez-Castejon, Gloria; Denes, Adam; Brough, David (Frontiers in Immunology, 2012)
Inflammation in the absence of infection (sterile inflammation) contributes to acute injury and chronic disease. Cerebral ischaemia is a devastating condition in which the primary injury is caused by reduced blood supply and is therefore sterile. The cytokine interleukin-1β (IL-1β) is a key contributor to ischaemic brain injury and central inflammatory responses. The release of IL-1β is regulated by the protease caspase-1, and its activating complex, the inflammasome. Of the known inflammasomes the best characterised, and one that is perceived to sense sterile injury is formed by a pattern recognition receptor called NLRP3. A key feature of NLRP3-inflammasome dependent responses in vitro in macrophages is the requirement of an initial priming stimulus by a pathogen (PAMP), or damage associated molecular pattern (DAMP) respectively. We sought to determine the inflammatory responses of NLRP3-activating DAMPs on brain derived mixed glial cells in the absence of an initial priming stimulus in vitro. In cultured mouse mixed glia the DAMPs ATP, MSU and CPPD crystals had no effect on the expression of IL-1α or IL-1β and induced release only when the cells were primed with a PAMP. In the absence of priming, these DAMPs did however induce inflammation via the production of IL-6 and CXCL1, and the release of the lysosomal protease cathepsin B. Furthermore, the acute phase protein serum amyloid A (SAA) acted as a priming stimulus on glial cells resulting in levels of IL-1 expression comparable to those induced by the PAMP LPS. In vivo, after cerebral ischaemia, IL-1 production contributed to increased IL-6 and CXCL1 since these cytokines were profoundly reduced in the ischaemic hemispheres from IL-1α/β double KO mice, although injury-induced cytokine responses were not abolished. Thus, DAMPs augment brain inflammation by directly stimulating production of glial derived inflammatory mediators. This is markedly enhanced by DAMP-induced IL-1-release-dependent responses that requi